Load Characteristics and Extreme Response of Straight-Bladed Floating VAWT Using a Fully Coupled Model - Luo, Wenping; Liu, Weiqin; Yang, Meng; Chen, Shuo; Song, Xuemin; Wu, Weiguo (Journal of marine science and engineering, 2023)
Operating Offshore Floating Vertical Axis Wind Turbines (OF-VAWT) have the potential to perform well in the deep-sea area. Some researchers gave performance prediction by developing simplified computing models. However, these models have imperfections in considering load and motion nonlinearity, especially in extreme environments. In this work, a numerical model is developed composed of Computational Fluid Dynamics (CFD) and Dynamic Fluid Body Interaction (DFBI) to acquire the aero-hydrodynamic load and performance of OF-VAWT in general and extreme environments. Unsteady Reynolds-Averaged Navier-Stokes (URANS), SST k-ω and Eulerian Multi-Phase (EMP) models are combined to generate a gas-liquid two-phase flow field; the Volume of Fluid (VOF) model is employed to capture free-surface and make numerical wind-wave. DFBI superposition motion technology is proposed for local motion definition and motion solution, and overset with sliding meshes is introduced to achieve the grid motion. The numerical approach is verified by the tunnel and tank experimental data from the available literature. Simulation results of general cases, such as variable wind speed, wave height and wave length, are compared to discuss the effect of environmental parameters on load and performance. Comparison shows that this straight-bladed OF-VAWT is more susceptible to wind speed. Furthermore, the aerodynamic load generated by the shut-down rotor is still significant in extreme environment, which has implications for the development of OF-VAWT controller.